SISTEM REPOSITORI DAN PENGARSIPAN UNTUK MANAJEMEN PENYIMPANAN DATA SURAT RESMI PADA DESA KARANGDUREN KABUPATEN MALANG - Yuri Ariyanto; Atiqah Nurul Asri; Dwi Puspitasari; Yoppy Yunhasnawa; Faiz Ushbah Mubarok (P3M Politeknik Negeri Malang, 2022)
At the village level, there are many obstacles faced by village government officials in their efforts to provide services to the community. One of which is storing official letters that have been issued by the Village Office. So far, official letter storage at the village office was still in the form of hard files (paper) and stacked on storage shelves, without any soft files and filing numbers. With such a letter storage model, as a result, the village office correspondents had difficulty especially in finding the letter if needed. Therefore, a Repository and Archiving System for Data Storage Management of Official Letters was created so as to improve the service and efficiency of the Karangduren Village Office's performance in serving the community. In other words, this PPM (Community Service) activity produced a prototype repository and archiving system application for data storage management for official letters at the Karangduren Village Office, Kec. Pakisaji, Kab. Malang, by involving all members of the PPM team for its implementation. Students were involved in survey activities to analyze system requirements in Karangduren Village, Pakisaji Sub-district, Malang Regency and making application usage modules.